Nucleus-encoded plastid sigma factor SIG3 transcribes specifically the psbN gene in plastids - Zghidi, Wafa (Oxford University Press, 2007)
We have investigated the function of one of the six plastid sigma-like transcription factors, sigma 3 (SIG3), by analysing two different Arabidopsis T-DNA insertion lines having disrupted SIG3 genes. Hybridization of wild-type and sig3 plant RNA to a plastid specific microarray revealed a strong reduction of the plastid psbN mRNA. The microarray result has been confirmed by northern blot analysis. The SIG3-specific promoter region has been localized on the DNA by primer extension and mRNA capping experiments. Results suggest tight regulation of psbN gene expression by a SIG3-PEP holoenzyme. The psbN gene is localized on the opposite strand of the psbB operon, between the psbT and psbH genes, and the SIG3-dependent psbN transcription produces antisense RNA to the psbT–psbH intergenic region. We show that this antisense RNA is not limited to the intergenic region, i.e. it does not terminate at the end of the psbN gene but extends as antisense transcript to cover the whole psbT coding region. Thus, by specific transcription initiation at the psbN gene promoter, SIG3-PEP holoenzyme could also influence the expression of the psbB operon by producing psbT antisense RNA.